An interchangeable role for kainate and metabotropic glutamate receptors in the induction of rat hippocampal mossy fiber long‐term potentiation in vivo. Issue 11 (25th April 2015) - Wallis, James L.; Irvine, Mark W.; Jane, David E.; Lodge, David; Collingridge, Graham L.; Bortolotto, Zuner A.
ABSTRACT The roles of both kainate receptors (KARs) and metabotropic glutamate receptors (mGluRs) in mossy fiber long‐term potentiation (MF‐LTP) have been extensively studied in hippocampal brain slices, but the findings are controversial. In this study, we have addressed the roles of both mGluRs and KARs in MF‐LTP in anesthetized rats. We found that MF‐LTP could be induced in the presence of either GluK1‐selective KAR antagonists or group I mGluR antagonists. However, LTP was inhibited when the group I mGluRs and the GluK1‐KARs were simultaneously inhibited. Either mGlu1 or mGlu5 receptor activation is sufficient to induce this form of LTP as selective inhibition of either subtype alone, together with the inhibition of KARs, did not inhibit MF‐LTP. These data suggest that mGlu1 receptors, mGlu5 receptors, and GluK1‐KARs are all engaged during high‐frequency stimulation, and that the activation of any one of these receptors alone is sufficient for the induction of MF‐LTP in vivo. © 2015 The Authors Hippocampus Published by Wiley Periodicals, Inc.